Imaging Evaluation of Periarticular Soft Tissue Masses in the Appendicular Skeleton: A Pictorial Review - Francesco Pucciarelli; Maria Carla Faugno; Daniela Valanzuolo; Edoardo Massaro; Lorenzo Maria De Sanctis; Elisa Zaccaria; Marta Zerunian; Domenico De Santis; Michela Polici; Tiziano Polidori; Andrea Laghi; Damiano Caruso (Journal of Imaging, 2025)
Soft tissue masses are predominantly benign, with a benign-to-malignant ratio exceeding 100:1, often located around joints. They may be contiguous or adjacent to joints or reflect systemic diseases or distant organ involvement. Clinically, they typically present as palpable swellings. Evaluation should consider duration, size, depth, and mobility. Also assess consistency, growth rate, symptoms, and history of trauma, infection, or malignancy. Laboratory tests are generally of limited diagnostic value. The primary clinical goal is to avoid unnecessary investigations or procedures for benign lesions while ensuring timely diagnosis and treatment of malignant ones. Imaging plays a central role: it confirms the presence of the lesion, assesses its location, size, and composition, differentiates between cystic and solid or benign and malignant features, and can sometimes provide a definitive diagnosis. Imaging is also crucial for biopsy planning, treatment strategy, identification of involved structures, and follow-up. Ultrasound (US) is the first-line imaging modality for palpable soft tissue masses due to its low cost, wide availability, and lack of ionizing radiation. If findings are inconclusive, magnetic resonance imaging (MRI) or computed tomography (CT) is recommended. This review aims to discuss the most common causes of periarticular soft tissue masses in the appendicular skeleton, focusing on clinical presentation and radiologic features.